KEDUDUKAN ISTRI DALAM RUMAH TANGGA DI TINJAU DARI UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN (STUDI KASUS DI DESA WEWIT KECAMATAN ADONARA TENGAH) - Amir, Ariyansa; Hedewata, Agustinus; Pello, Helsina Fransiska (Petitum Law Journal, 2023)
This research aims to find out how the wife's position in the household in Wewit Village, Central Adonara District, in terms of Law Number 1 of 1974 concerning Marriage and what are the legal consequences of the position of the wife's rights and obligations in the household in Wewit Village, Adonara District Currently being reviewed is Law Number 1 of 1974 concerning marriage. The research method used by researchers is a type of empirical research, namely research carried out directly in the field, namely by engaging directly with participants, which is related to the formulation of the research problem being studied. The data sources used are the legal sources and materials used are primary legal materials and secondary legal materials. The results of the research show that 1) the position of the wife in the tanges household is equal or balanced with the husband, the rights and obligations of the wife in the household are to earn a living physically and mentally, take care of the household as well as possible, get a dowry, have the right to good treatment from her husband, obey husband's orders and serves the husband's biological needs. 2) the legal consequences of the position of the wife's rights and obligations in the household, namely that the husband may file for divorce (one) if the wife's rights and obligations are not carried out in the household and vice versa, the wife can also file a divorce suit against the husband if the husband does not carry out his rights and obligations properly. Good. The husband must give a warning (tauji) to the wife to immediately change her attitude in carrying out her duties as a wife in the household.